A series of lay sermons on good principles and good breeding - Hogg, James, 1770-1835 (Hogg, James, 1770-1835. Works. 1995, 1997)
Lay Sermons offers, playfully, a series of lay sermons on good principles and good breeding: the very last thing that one would expect to come from the pen of the famous Ettrick Shepherd of Blackwood's. But a significant part of the joke is that the Shepherd, most unexpectedly, provides lay sermons that combine into a series of wise meditations on life and on literature. This important text by a major Scottish writer has long been neglected and undervalued, partly because it has not been easily accessible. However, recent critics such as Robert Kiely, David Groves and Silvia Mergenthal have pointed to the interest and influence of Hogg's Lay Sermons; and this new edition by Gillian Hughes will make the book readily available for the first time since the 1830s.